A Molecular Epidemiological Survey of Clinically Important Dermatophytes in Iran Based on Specific RFLP Profiles of Beta-tubulin Gene - Mahdi Abastabar; Ali Rezaei -Matehkolaei; Mohammad Reza Shidfar; Parivash Kordbacheh; Rasoul Mohammadi; Tahereh Shokoohi; Mohammad Taghi Hedayati; Nilufar Jalalizand; Hossein Mirhendi (Tehran University of Medical Sciences, 2013)
Background: Surveillance of dermatophytosis is essential to determine the likely changes in etiological trends and distribution profile of this infection. In this study beta tubulin gene (BT2), was used as the first time in a PCR-RFLP format to clarify the distribution of dermatophytosis agents in some parts of Iran.Methods: A total of 603 clinical isolates was obtained from 500 patients in Tehran, Isfahan, Mazandaran and Guilan provinces. The isolates were identified using macro/micro-morphological criteria and electrophoretic patterns of PCR amplicons of BT2after digestion with each of the restriction enzymes FatI, HpyCH4V, MwoI and Alw21I.Results: Among the patients, 59.2% were male and 40.8% female. The most prevalent clinical form was tinea pedis (42.4%), followed by tinea cruris (24.2%), tinea unguium (12.3%), tinea corporis (10.8%), tinea faciei (4%), tinea manuum (3.14%), tinea capitis (3%) and tinea barbae (0.16%), respectively. Trichophyton interdigitale ranked the first, followed by T. rubrum, Epidermophyton floccosum, Microsporum canis, T. tonsurans, T. erinacei and T. violaceum (each 0.49%) and the less frequent species were T. schoenleinii, M. gypseum and T. anamorph of Arthroderma benhamiae (each 0.16%). A case of scalp infection by E. floccosum was an exceptional event in the study. No case of T. verrucosum was found.Conclusion: Trichophyton species and E. floccosum are yet the predominant agents of infection in Iran, while Microsporum species are decreasing. T. interdigitale and Tinea pedis remain as the most causal agent and clinical form of dermatophytosis, respectively. It seems that BT2 can be a useful genetic marker for epidemiological survey of common pathogenic dermatophytes.